Challenges of the vegetable and fruit market - Domján, E.; Fekete Farkas, M. (International Journal of Horticultural Science, 2011)
The situation of the horticulture sectors have been in the limelight of the professional and economic decision makers all over Europe. This article analyses the situation of the sector from economic point of view and reveals the main reasons of its low income and high risk. It concludes that one of the biggest problems is the trading uncertainty in the vegetable and fruit sector that is caused by the asymmetric market structure of the post-regime era. Since sizes of vegetable and fruit plantations do not allow producers to supply individually the extremely concentrated food retail trade or the processing trade they must find alternative ways for trading their products. The study introduces two alternative solutions. One alternative is foundation of modern multi-level producer co-operatives with the help of EU subsidies. Secondary and tertiary co-operatives may achieve better market position and lower trading price risk with managing production, professional marketing, and improving the information flow. The other alternative is searching for new trading channels such as local provision, restructuring of local markets, and direct trade (home delivery and pick-it-yourself programmes). The shorter producer-consumer distance means better quality at lower price for customers and income in the case of smaller amount of products for producers. It is concluded that both solutions together or separately may help individual producers in their trading problems. However, whichever way they choose, producers must co-operate.